Recent advances in heteroleptic multiple-stranded metallosupramolecules. Issue 34 (14th August 2020) - Tran, Ngoc Minh; Yoo, Hyojong
Abstract : Recent advances in the development of heteroleptic multiple-stranded metallosupramolecules. Abstract : Well-ordered combination of defined coordination spheres and multiple types of ligands (heteroleptic) in a given structure can expand the structural complexity and functional diversity of the resulting metallosupramolecules. Such heteroleptic metallosupramolecular architectures are expected to afford advanced utility in a variety of applications. In this concise review article, recent advances in the development of multi-nuclear-cluster-based heteroleptic multiple-stranded (HLMS) metallosupramolecules are summarized and demonstrated. To construct HLMS metallosupramolecules, one type of multitopic ligands can be employed for building up multiple strands, while another type of ligands can be utilized to construct multi-nuclear clusters. Most HLMS metallosupramolecules adopt helical geometries and have high molecular symmetry, which can be key factors for the structural completion. HLMS metallosupramolecules can be used as basic building blocks for the fabrication of higher-order polymeric or discrete assembly architectures with well-defined geometries.